Pro-and Anti-vaccination among Mothers in Deciding Children’s Immunization: A Qualitative Study - Izzati, Aisyah Nur; Indarwati, Retno; Makhfudli, Makhfudli; Utomo, Budi; Has, Eka Mishbahatul M.; Arief, Yuni Sufyanti; Arifin, Hidayat (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Society participation in the mandatory basic immunization program has declined in the last 2 years in Indonesia. One of the causes is the widespread of anti-vaccine issue, which has recently been debated on social media. This study aimed to explore the perspectives, backgrounds, experiences, and aspects that underlie the mother’s confidence in anti-vaccine and pro-vaccine groups who join the Facebook social media forum. METHODS: A phenomenology qualitative design was undertaken. The data were collected from June to August 2020. We conducted in-depth structured interviews with 5 anti-vaccine participants and 5 pro-vaccine participants. We obtained saturation data with ten participants. The data managed by NVIVO 12 software and analyzed using the thematic analysis method. RESULTS: We obtained 4 themes, including social media values, perceptions of immunization, immunization barriers, and knowledge about immunization. Anti-vaccine parents were firm not to immunize their children even though they knew the purpose of immunization and were perceived that there were no barriers to taking immunization. Pro-vaccine parents were determined to take basic immunization despite experiencing various barriers. CONCLUSION: This study showed that social media, perceptions, knowledge, and barrier about immunization affect mothers in considering the decision to give immunization to their children. Nurses and other healthcare workers should be provided positive communication and mutual trust between parents and health services are required to develop parental vaccine confidence so that basic immunization coverage can increase.